Pengaruh COVID-19 Terhadap Kegiatan Ekspor Impor di Indonesia - Diva Permata Tri Putri; Eva Wina Aprielya Damayanti; Intan Sianturi (Politeknik Ilmu Pelayaran Semarang, 2021)
The Covid-19 pandemic has fatal consequences for the world economy, one of which occurred in Indonesia. Government regulations require the public to apply health protocols that must be obeyed, namely social distancing which causes traders to be hampered in the process of buying and selling activities. The purpose of this study is to analyze the impact of Covid-19 on export-import activities in Indonesia. This research method uses the desk study method, namely the collection of data sourced from secondary data obtained from BPS in 2020. The results show that: Covid-19 has had an impact including: (1) The largest decline in the value of imports in Indonesia was experienced in February 2020 and May 2020; (2) Document processing must take longer due to this pandemic and all import-export activities must be guided by health protocols that must be carried out; (3) Delay in handling the ship at the port (ship delay), which will have an impact on the delay of the goods arriving at the hands of the owner of the goods (importer) which causes the importer to also have to prepare more costs for importing the goods.